2003
DOI: 10.1074/jbc.m303888200
|View full text |Cite
|
Sign up to set email alerts
|

Redox Regulation of a Novel L1Md-A2 Retrotransposon in Vascular Smooth Muscle Cells

Abstract: Activation and reintegration of retrotransposons into the genome is linked to several diseases in human and rodents, but mechanisms of gene activation remain largely unknown. Here we identify a novel gene of L1Md-A2 lineage in vascular smooth muscle cells and show that environmental hydrocarbons enhance gene expression and activate monomer-driven transcription via a redox-sensitive mechanism. Site-directed mutagenesis and progressive deletion analyses identified two antioxidant/electrophile response-like eleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 52 publications
2
48
0
Order By: Relevance
“…Expression of L1 retrotransposon sequences is up-regulated in mouse somatic cells challenged acutely with BaP or its oxidative metabolites as determined by Northern blot analysis, differential display, and realtime PCR (27)(28)(29). To determine if BaP treatment activates human L1 expression and increases L1 retrotransposition, a plasmid-based strategy was employed using cultured HeLa cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Expression of L1 retrotransposon sequences is up-regulated in mouse somatic cells challenged acutely with BaP or its oxidative metabolites as determined by Northern blot analysis, differential display, and realtime PCR (27)(28)(29). To determine if BaP treatment activates human L1 expression and increases L1 retrotransposition, a plasmid-based strategy was employed using cultured HeLa cells.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we reported that expression of L1 retrotransposon sequences is dramatically up-regulated in mouse vascular smooth muscle cells challenged with BaP or its oxidative metabolites as determined by Northern blot analysis, differential display, and DNA microarrays (27)(28)(29). Moreover, a novel retrotransposon of mouse L1Md-A2 lineage was found in vascular smooth muscle cells that contain two antioxidant responsive elements in its 5V -UTR region and participate in transactivation (29).…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…48,52 Particularly interesting is the correlation between elevated levels of certain endogenous retroviral transcripts in myocardium and cardiovascular disease in rats, 53,54 and the suggestion that L1Md may be involved in atherogenesis. 55 EZR1 transcript abundances were dose-dependently increased by doses of TCDD that cause cardiovascular toxicity and disrupted cardiomyocyte gene expression. 4 Regardless, the evidence indicates that TCDD induction of EZR1 involves activation of a zebrafish NF-jB-like factor.…”
Section: Biological Implications Of Ezr1 Expressionmentioning
confidence: 99%